Young, gifted and missing : the underrepresentation of African American males in science, technology, engineering and mathematics disciplines - Robins, Anthony G.; Knibbs, Locksley; Ingram, Ted N.; Weaver, Michael N., Jnr; Hilton, Adriel A. (Diversity in higher education, 2022)
Acting as a bridge between the academic and policymaking communities, Young, Gifted and Missing sets the stage for addressing critical issues around why African American men are absent in the STEM disciplines.